An early nonsense mutation facilitates the expression of a short isoform of CNGA3 by alternative translation initiation. (June 2018) - Täger, Joachim; Kohl, Susanne; Birch, David G.; Wheaton, Dianna K.H.; Wissinger, Bernd; Reuter, Peggy
Abstract: The cyclic nucleotide-gated (CNG) channel - composed of CNGA3 and CNGB3 subunits - mediates the influx of cations in cone photoreceptors after light stimulation and thus is a key element in cone phototransduction. Mutations in CNGA3 and CNGB3 are associated with achromatopsia, a rare autosomal recessive retinal disorder. Here, we demonstrate that the presence of an early nonsense mutation in CNGA3 induces the usage of a downstream alternative translation initiation site giving rise to a short CNGA3 isoform. The expression of this short isoform was verified by Western blot analysis and DAB staining of HEK293 cells and cone photoreceptor-like 661W cells expressing CNGA3-GST fusion constructs. Functionality of the short isoform was confirmed by a cellular calcium influx assay. Furthermore, patients carrying an early nonsense mutation were analyzed for residual cone photoreceptor function in order to identify a potential role of the short isoform to modify the clinical outcome in achromatopsia patients. Yet the results suggest that the short isoform is not able to compensate for the loss of the long isoform leaving the biological role of this variant unclear. Highlights: Alternative translation initiation results in a short isoform of CNGA3. This CNGA3 isoform retains functional activity as observed by a calcium influx assay. The short CNGA3 isoform is expressed in cone photoreceptor-like 661W cells. The expression of this CNGA3 isoform was also observed in injected zebrafish larvae.